LES INSTRUMENTS DE MUSIQUE AU BAS-CONGO ET DANS LES REGIONS AVOISINAN- TES: Par Bertil Soderberg. Stockholm: Ethnographical Museum of Sweden, monograph series, publication No. 3, 1956. Pp. 284; 26 plates; 25 text-diagrams; 1 map. 60 kroner (International Library of African Music, 1957)
pages: 61
Keywords: African Music